EVALUATION OF THE INTEGRATED EPIDEMIOLOGICAL SURVEILLANCE SYSTEM FOR DISEASES AT THE ALAK COMMUNITY HEALTH CENTER, KUPANG CITY - Landi, Soleman; Wahyuni, Maria Magdalena Dwi; Duli, Maria Alfonsia Deran; Pandie, Erlian Mariana; Setiawan, Thirza Khalilah Putri; Wellem, Tamariska Priscilla Pristin Wellem (JURNAL WIDYA MEDIKA, 2026)
An integrated epidemiological surveillance system plays a crucial role in supporting early detection and public health response at the primary healthcare level. This study aimed to describe the implementation of the Integrated Epidemiological Surveillance System for diseases at Alak Primary Health Center, Kupang City, in 2025. The study employed a qualitative descriptive approach using in-depth interviews with five purposively selected informants, consisting of three key informants (the epidemiological surveillance program officer and two surveillance staff) and two supporting informants (a health information system officer and a laboratory officer). Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. Key findings indicate that the implementation of surveillance was supported by the availability of trained surveillance personnel, adequate operational funding, and the utilization of supporting facilities such as electronic medical records, surveillance applications, and manual reporting forms. The system has integrated indicator-based surveillance and event-based surveillance for communicable diseases, as well as the use of the ASIK application for monitoring non-communicable diseases. Data processing and analysis were conducted routinely based on person, place, and time variables and were utilized in monthly evaluations. Surveillance information was disseminated through weekly bulletins, reports to the District Health Office, and information media at the primary health center. The main challenge identified was the limited availability of supporting equipment, particularly computers, which affected the timeliness of reporting. Strengthening infrastructure and technical capacity is essential to enhance the effectiveness of surveillance in supporting early detection and public health response.